IMPLEMENTATION OF THE POLICY OF THE NORTH KAYONG REGENCY REGIONAL GOVERNMENT IN INCREASING RICE PRODUCTIVITY IN SIMPANG HILIR DISTRICT - Rusmayanti Rusmayanti (Sean Institute, 2022)
The Regional Government has an obligation to provide food or rice for the community. One of the efforts to provide food or rice for the community is through increasing rice productivity. In Simpang Hilir District, rice productivity is still around 24.03-25.68 ku/ha. This study uses Edward III's Theory to make it easier to identify the determinants of policy implementation implemented by the Agriculture and Food Service (Dispangan) to increase rice productivity, namely: communication, resources, disposition and bureaucratic structure. This qualitative research uses descriptive data analysis by determining data sources through a purposive method. Data sources consist of primary data with 12 participants and 4 triangulation participants as well as secondary data in the form of data from Dispangan, literature and relevant previous research results. Primary data collection techniques through interviews were analyzed using the open code 4.03 application. The results of the research in the implementation of policies to increase rice productivity in Simpang Hilir Sub-District involved many parties, namely the Agriculture and Food Service, related regional apparatus organizations, fertilizer distributors and farmer groups, so that coordination is needed; the complexity of policies to increase rice productivity so that it requires consensus to achieve goals more easily; the limited authority of Dispangan in providing resources so that cooperation with the related OPD is required; and the tendency of farmers not to follow the instructions for rice cultivation technology so that rice productivity is not optimal.